ANALISIS PERILAKU KONSUMEN TERHADAP KEPUASAN MEMILIH PRODUK ORIFLAME PADA PT. ORINDO ALAM AYU CABANG MEDAN (ORIFLAME) - Vina Maria Ompusunggu; Rikawati Ginting Munthe (JURNAL REGIONOMIC, 2020)
Consumer behavior is part of human-related marketing management. Consumer behavior is not the same and changes all the time, so consumer behavior in choosing satisfaction must be studied continuously. Therefore, the researcher wants to learn about the consumer behavior of Oriflame, which is a cosmetics company that offers different types of cosmetics with high quality and natural. Oriflame is a cosmetics company that offers high-quality natural cosmetics and skin care products through a network of independent sales forces that is different from the retail system in general.This study aims to determine consumer behavior in satisfaction in choosing cosmetic products at PT Orindo Alam Ayu (Oriflame) Medan Branch. This study uses a descriptive research method with a qualitative approach. Data collection and determining the level of development are carried out by means of collecting data by means of questionnaires, interviews, observation and documentation. The data analysis technique used is descriptive qualitative by going through several processes such as data verification, data reduction, data presentation, and drawing conclusions. The results showed that the informants felt satisfaction in using Oriflame products as much as 66.7% and would recommend to other parties to choose Oriflame products as both beauty products and health products as much as 67.6%. Consumer behavior towards satisfaction in choosing oriflame products at PT. Orindo Alam Ayu Branch Medan is influenced by four factors, namely (1) social factors, (2) personal factors, (3) psychological factors and (4) cultural factors.